2017
DOI: 10.1111/voxs.12382
|View full text |Cite
|
Sign up to set email alerts
|

Platelets in liver regeneration

Abstract: Background and Objectives Loss of liver tissue leading to impairment of liver function represents a major cause of mortality. Understanding the mechanism of liver regeneration and developing therapies to sustain liver regeneration are of high therapeutic relevance. In this regard, platelets are considered as potential candidates for stimulating liver regeneration.Methods We aim to review the most recent evidence regarding the role of platelets in liver regeneration.Results Platelets stimulate liver regeneratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 146 publications
(155 reference statements)
1
21
1
Order By: Relevance
“…24,27 The implication of platelets in liver regeneration recently gained considerable interest. [28][29][30] Robust data reporting the relationship between platelet count and the occurrence of PHLF in patients undergoing liver surgery is lacking, and results obtained from animal models do not necessarily reflect what takes place in humans.…”
Section: Introductionmentioning
confidence: 99%
“…24,27 The implication of platelets in liver regeneration recently gained considerable interest. [28][29][30] Robust data reporting the relationship between platelet count and the occurrence of PHLF in patients undergoing liver surgery is lacking, and results obtained from animal models do not necessarily reflect what takes place in humans.…”
Section: Introductionmentioning
confidence: 99%
“…The release of granule contents during platelet activation has been suggested to trigger liver regeneration. Notably, it was suggested that platelet serotonin, vascular endothelial growth factor, HGF, and insulin like‐growth factor are involved …”
Section: Liver Regenerationmentioning
confidence: 99%
“…This has major consequences for patients with extended oncological diseases that cannot benefit from liver resection. (119,120) Platelets have been shown to contribute to liver regeneration in many ways (13)(14)(15) (Fig. 1).…”
Section: Liver Regenerationmentioning
confidence: 99%
See 2 more Smart Citations